PENGEMBANGAN APLIKASI PELAYANAN RUMAH SAKIT BERBASIS SMS GATEWAY DI RSUD KABUPATEN BULELENG - Gede Edy Priyadnya (Universitas Pendidikan Ganesha, 2012)
This research aimed at: (1) designing the application of hospital service based on SMS gateway at general hospital in Buleleng regency; (2) implementing the application of hospital service based on SMS gateway at general hospital in Buleleng regency. The output of this system would be an application which gives health services to the patients or other people about medical check-up schedule of the outpatients, doctor’s present list in the hospital, information of the patients’ room, and information about health support like health education, social services and information about government health programs (ASKES, JKBM, and Jamkesmas). In designing this application used Waterfall Method, or as known as Classic Life Cycle Model. This Waterfall Model is a classic model which systematic or consecutively in constructing software. This model consists of several stages. Those are (1) requirements definition, (2) system and software design, (3) implementation and unit testing, (4) integration and system testing, and (5) operation and maintenance. The result of this study is the application of hospital service based on SMS gateway which was implemented with PHP, MySQL as the database server and Gammu as the tool server of SMS Gateway. The result of the test that had been done showed that this application run well as expected. With the presence of this application, public services at general hospital in Buleleng regency were increased. The patients or other people were easy to get up-to-date information from the hospital through their cell phone.